Extending Temperament-Based, Data-Driven Profiles of Attention-Deficit/Hyperactivity Disorder to Dual-Treatment-Seeking Hispanic/Latine Youths - Katherine M. Schmarder; Cameron Riopelle; Min Zhu; Stephanie S. J. Morris; Kathleen E. Feeney; Jessica N. Smith; Erica D. Musser (Clinical Psychological Science, 2026)
Attention-deficit/hyperactivity disorder (ADHD) nosology lacks biological and predictive validity, temporal stability, and ability to capture heterogeneity in emotional functioning, executive function, and/or reward sensitivity. Prior work has addressed limitations in current practice by data-driven temperament profiles (mild, surgent, irritable) in a largely White, non-Hispanic/Latine (88%), community-recruited sample. In the present study, we extend this work to a predominantly Hispanic/Latine (80%), clinically recruited sample. Participants (youths, 5–13 years: N = 177; ADHD: n = 96) were recruited from a double-masked, crossover, dual-treatment study. Three- and four-profile solutions demonstrated the best fit. The three-profile solution generally replicated the original work with mild, surgent, and irritable profiles. The four-profile solution divided the mild and irritable profiles from the three-profile solution, resulting in low/mild, mildly irritable, irritable, and surgent profiles. Profile differences in autonomic-nervous-system activity (electrodermal activity, respiratory sinus arrhythmia during an emotional task) were not observed. Clinical implications and future directions are discussed.